Morphological Processes in the Kwarta Mataci Dialect of Karekare (West Chadic): Evidence from Affixation, Infixation, and Tonal Modification - Musa Yahuza Danhausa; Bukar Isa Gamawa; Fatima Bala Haladu (RaSAIL Media Group, Semarang, Indonesia, 2026)
This study examines morphological processes in the Kwarta Mataci dialect of the Karekare language, one of the West Chadic languages that remains poorly documented in northeastern Nigeria. The unit of analysis in this study is morphologically complex words, obtained from native speakers through field-based oral interviews and supported by secondary linguistic sources. This study aims to provide a systematic description of word-formation strategies in the Kwarta Mataci dialect, with a focus on affixation, infixation, and tonal modification. Data were collected from educated and uneducated speakers and analyzed using a descriptive linguistic approach based on the framework of Matthews (1993) and the morphological process model of Abubakar (2001). The results show that the Kwarta Mataci dialect makes productive use of prefixation and suffixation in derivation and plural marking, as well as reduplication for intensifying meaning. An important finding of this study is the presence of productive infixation (-gwa-) as a word-formation strategy, a process that is relatively rarely reported in Chadic languages. In addition, tonal variations have been shown to function morphologically, marking shifts in word classes and meaning contrasts, suggesting a close interaction between morphology and tone. These findings provide new empirical evidence regarding infixation and morphophysiological processes in the Karekare language. Overall, this study contributes to the morphological typology of West Chadic by presenting the first dialect-specific description of the morphology of Kwarta Mataci and by expanding understanding of the aphasic organization and tonal morphology in poorly documented Afro-Asiatic languages.